Computational methods in multiphase flow IV - International Conference on Computational Methods in Multiphase Flow (4th : 2007); Mammoli, A. A. (Andrea Alberto); Brebbia, C. A.; Wessex Institute of Technology (Southampton : WIT)
Includes bibliographical references and index